Thermodynamic Property Model of Wide-Fluid Phase Propane - Astina, I Made; Firmansyah, Juristiawan (ITB Journal Publisher, LPPM ITB, 2007)
A new thermodynamic property model for propane is expressed in form of the Helmholtz free energy function. It consists of eight terms of the ideal-gas part and eighteen terms of the residual part. Accurate experimental data of fluid properties and theoretical approach from the intermolecular potential were simultaneously considered in the development to insure accuracy and to improve reliability of the equation of state over wide range of pressures and temperatures. Based on the state range of experimental data used in the model development, the validity range is judged from the triple-point of 85.48 K to temperature of 450 K and pressure up to 60 MPa. The uncertainties with respect to different properties are estimated to be within 0.03% in ideal-gas isobaric specific heat, 0.2% in liquid phase density, 0.3% in gaseous phase density 1% in specific heats, 0.1% in vapor-pressure except at very low temperatures, 0.05% in saturated-liquid density, 0.02% in speed of sound of the gaseous phase and 1% in speed of sound of the liquid phase.